Orientasi matlamat pencapaian dan keresahan pelajar felda terhadap matematik - Wan Hassan, Wan Hardiana (2013)
This study was conducted to identify the level of motivation, confidence and anxiety in the FELDA students grades 4 to mathematics. The study involved 276 respondents from Form Four students in four secondary school in Kota Tinggi district. The respondents were chosen at random. Data collected through the questionnaire as a research instrument. Quantitative data were analyzed in the form of mean, percentage, frequency and standard deviation using SPSS (Statistical Package for Social Science) Version11.0 for Windows. A pilot study was conducted on 40 respondents and the reliability of the instrument is a = 0.77. The results showed that the level of motivation, confidence and anxiety Felda students form four students in the low mean score of 2.92 for the level of self-motivation, the mean score of 2.70 for the selfconfidence and mean scores 3:57 is the medium for the form four students' anxiety toward mathematics. Analysis of the level of motivation, confidence and anxiety Felda students based on gender showed significant differences between males and females but it is not obvious